Impact of copper sulphate toxicity on plasma electrolytes of a freshwater teleost fish, Cyprinus carpio var. communis - Priya, K; Dinesh, K P B; Ramesh, M; Manavalaramanujam, R (Indian Journal of Fisheries, 2011)
The present paper deals with the changes in plasma electrolyte levels (Na*,K* & CI") of fish Cyprinus carpio when exposed to acute and sublethalconcentrations of copper sulphate. In both the treatments, sodium and chloridelevels declined significantly, whereas potassium level elevated. Comparing thetreatments, the alterations in electrolyte levels were found high in sublethaltreatment. The probable reasons governing the facts are interpreted anddiscussed in the light of earlier literature.